Assessing the efficiency and managing the performance of Greek tax offices - Katharaki, Maria; Tsakas, Marios (Journal of Advances in Management Research, 2010)
PurposeThe aim of this paper is to study the technical and scale efficiency of a set of tax offices (Inland Revenue) in Greece during the period 2001‐2006. Design/methodology/approachThe methodology used to estimate efficiency scores and Greek tax office ranking was the data envelopment analysis. In addition window analysis was used to detect efficiency trends and stability over time. Tobit analysis was applied to explain whether non‐discretionary factors play a role in tax office's performance. FindingsThe results underline that “scale size” and the structure of regional economy where tax offices operate are important factors affecting their efficiency. Research limitations/implicationsDespite the limitations related to the data set, the empirical work suggests that future research may need to concentrate on the dynamic factors i.e. characteristics of the regional where the tax office is situated which could play a significant role in a tax office performance. Practical implicationsThe analysis provides information on tailor‐made political and administrative measures that can lead to improvements in the general infrastructure behind the tax office system in Greece. Originality/valueConsidering that the emerging results needed to be evaluated and considered with a sceptical eye, the present study simply highlights the importance of the information (without sensationalizing it) from the policymakers' perspective and in so doing perhaps provide an additional information resource on which they can base their decisions and policies. © 2010, Emerald Group Publishing Limited.